Becoming Abraham Lincoln: The Coming of Age of Our Greatest President - Richard Kigel (Skyhorse Publishing, 2017)
Becoming Abraham Lincoln: The Coming of Age of Our Greatest President tells the true story of how this great American hero grew up and became a man. The story begins with Lincoln's cousin describing the murder of Abe's grandfather in 1782 by the Wabash Indians in the Kentucky wilderness. It ends as Lincoln turns twenty-five, downcast and debt-ridden after the failure of his first business venture, as he earns his first election victory to take his seat in the Illinois State Legislature. This vivid, authentic account of Abraham Lincoln in his formative years is told by those who were there-his friends and family. Supported by rigorous research, Becoming Abraham Lincoln is an authentic account of Lincoln's childhood and adolescence in the actual words of those who knew him best. We see Lincoln as he was, according to law partner Billy Herndon, "just as he lived, breathed, ate and laughed in this world." The historic eyewitness testimony in these pages forms a rich, detailed narrative unmatched in all Lincoln literature.